2000
DOI: 10.1074/jbc.m006101200
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Pro-invasive Effect of the Serine Proteinase Inhibitor Tissue Factor Pathway Inhibitor-2 on Human Hepatocellular Carcinoma Cells

Abstract: We have previously shown that human liver myofibroblasts promote in vitro invasion of human hepatocellular carcinoma (HCC) cells through a hepatocyte growth factor (HGF)/urokinase/plasmin-dependent mechanism. In this study, we demonstrate that myofibroblasts synthesize the serine proteinase inhibitor tissue factor pathway inhibitor-2 (TFPI-2). Despite the fact that recombinant TFPI-2 readily inhibits plasmin, we show that it potentiates HGF-induced invasion of HCC cells and is capable of inducing invasion on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 29 publications
(20 reference statements)
4
29
0
Order By: Relevance
“…Whereas the role of TFPI-2 in thoracic malignancies has not been systematically evaluated, Lakka et al (2000) observed that antisense to TFPI-2 enhances migration and invasiveness of A549 lung cancer cells in vitro. Although these observations suggest that TFPI-2 inhibits the malignant phenotype of cancer cells of diverse histologies, recent experiments by Neaud et al (2000) as well as Shinoda et al (1999) have shown that TFPI-2 is a potent mitogen for hepatocarcinoma as well as vascular smooth muscle cells. Collectively, these data indicate that the effects of TFPI-2 in cancer cells may be highly complex, and tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the role of TFPI-2 in thoracic malignancies has not been systematically evaluated, Lakka et al (2000) observed that antisense to TFPI-2 enhances migration and invasiveness of A549 lung cancer cells in vitro. Although these observations suggest that TFPI-2 inhibits the malignant phenotype of cancer cells of diverse histologies, recent experiments by Neaud et al (2000) as well as Shinoda et al (1999) have shown that TFPI-2 is a potent mitogen for hepatocarcinoma as well as vascular smooth muscle cells. Collectively, these data indicate that the effects of TFPI-2 in cancer cells may be highly complex, and tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue factor also upregulated the production of vascular endothelial cell growth factor (Ollivier et al, 1998) and uPAR (Taniguchi et al, 1998) in tumor cells, and its levels perfectly correlated with the degree of tumor angiogenesis and progression in ®brosarcomas, melanomas, breast and pancreatic tumors (Contrino et al, 1996;Mueller et al, 1992;Nakagawa et al, 1998;Mueller and Ruf, 1998). Recently it was reported (Neaud et al, 2000) that human liver myo®broblasts promote in vitro invasion of human hepatocellular carcinoma (HCC) cells through a hepatocyte growth factor (HGF)/urokinase/plasmin-dependent mechanism. Myo®broblasts also synthesize the serine proteinase inhibitor tissue factor pathway inhibitor-2 (TFPI-2).…”
Section: Discussionmentioning
confidence: 99%
“…A matrigel cell invasion assay was performed as described previously (Neaud et al, 2000). Briefly, 8 mm polycarbonate pore size filters were coated with Matrigel (15 mg) and inserted into 12-well plates (Gibco).…”
Section: Functional Assaysmentioning
confidence: 99%